STUDY ON EXISTENCE THEORY FOR INTEGRAL EQUATIONS OF MIXED TYPE - Afrouzi, G. A.; Yousefi, S.; Talarposhti, R.A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
This article presents an existence of monotonic solution for the nonlinear mixed Volterra-Fredholm integral equation acting on L_1[0, 1]. By using the techniques of the De Blasi measure of weak noncompactness, we employ the basic fixed point theorems such as Darbo s theorem to obtain the mentioned aims in Banach spaces.